Diazoxide enhances excitotoxicity-induced neurogenesis and attenuates neurodegeneration in the rat non-neurogenic hippocampus. (1st October 2016) - Martínez-Moreno, M.; Batlle, M.; Ortega, F.J.; Gimeno-Bayón, J.; Andrade, C.; Mahy, N.; Rodríguez, M.J.
Highlights: Excitotoxicity transiently enhances KATP channel expression in the rat hippocampus. Diazoxide reduces NMDA-induced neuronal loss and microglial reaction in the hippocampus. Excitotoxicity induces neurogenesis and appearance of Sp8-positive cells in the lesioned non-neurogenic hippocampus. Diazoxide enhances neurogenesis processes in the lesioned hippocampus. KATP channel modulates neurogenesis in the adult CNS under inflammatory conditions. Abstract: Diazoxide, a well-known mitochondrial KATP channel opener with neuroprotective effects, has been proposed for the effective and safe treatment of neuroinflammation. To test whether diazoxide affects the neurogenesis associated with excitotoxicity in brain injury, we induced lesions by injecting excitotoxic N-methyl-d -aspartate (NMDA) into the rat hippocampus and analyzed the effects of a daily oral administration of diazoxide on the induced lesion. Specific glial and neuronal staining showed that NMDA elicited a strong glial reaction associated with progressive neuronal loss in the whole hippocampal formation. Doublecortin immunohistochemistry and bromo-deoxyuridine (BrdU)-NeuN double immunohistochemistry revealed that NMDA also induced cell proliferation and neurogenesis in the lesioned non-neurogenic hippocampus. Furthermore, glial fibrillary acidic protein (GFAP)-positive cells in the injured hippocampus expressed transcription factor Sp8 indicating that the excitotoxic lesion elicited the migration of progenitors from the subventricular zone and/or the reprograming of reactive astrocytes. Diazoxide treatment attenuated the NMDA-induced hippocampal injury in rats, as demonstrated by decreases in the size of the lesion, neuronal loss and microglial reaction. Diazoxide also increased the number of BrdU/NeuN double-stained cells and elevated the number of Sp8-positive cells in the lesioned hippocampus. These results indicate a role for KATP channel activation in regulating excitotoxicity-induced neurogenesis in brain injury.